Pengembangan Sistem Monitoring Kinerja FWG untuk Optimalisasi Produksi Air Tawar di Atas Kapal - Kurniawan, Edi; Sonhaji, Sonhaji; Ar-Ridho, Bayu Rahmiyarto (Universitas Hamzanwadi, 2024)
Fresh water is a basic need for ship crews to support smooth operations. An auxiliary aircraft that can produce fresh water on board is required to reduce operational costs, namely the Fresh Water Generator (FWG). This research aims to develop an FWG performance monitoring system to optimize freshwater production. The research model used is a prototype with design, modeling, and prototype formation stages. The system uses an Arduino Mega 2560 microcontroller to process data from temperature, pressure, and TDS sensors, which are then sent via the LoRa transmitter and received by the LoRa receiver. The data is processed by the ESP 32 microcontroller and displayed on the LCD. In real-time, it monitors critical parameters such as heater temperature, filter quality, and freshwater quality, enabling rapid problem detection and timely corrective action. The findings show that the FWG performance monitoring tool can optimize freshwater production; based on the test results, it can operate stably at a pressure of 0.44 bar and a maximum temperature of 84°C and can work reliably under extreme conditions, making the FWG more efficient in producing freshwater.